Seismic performance of earthquake resistant simple residential confined masonry house structure based on permen PUPR No.5 of 2016 specification. Issue 1 (April 2021) - A A Gumilang, S; Rusli, M
Abstract: This research focused on seismic performance evaluation of earthquake resistant simple landed house using Confined Masonry (CM) structural system which follows technical specifications set forth in regulation of Appendix 2 of Peraturan Menteri Pekerjaan Umum dan Perumahan Rakyat (Permen PUPR) Nomor 5 tahun 2016 (Permen PUPR No. 5 of 2016). The seismic performance evaluation of the structure is performed by conducting strength based analysis using earthquake loading as specified in SNI 1726:2019. Seismic performance evaluation of Unreinforced Masonry (URM) simple landed house was also performed to be compared. Evaluation result shows that CM house prototype which follows the regulation has good seismic performance. Meanwhile, URM house prototype is inadequate to resist earthquake loads particularly on many locations in Indonesia with moderate to high level of seismicity.